Investigadores colombianos en Brasil : características biosociodemográficas, indicadores de bienestar y síntomas de depresión, ansiedad y estrés - Bonilla Rubio, Maria Andrea (2016)
The present study investigates the biosociodemographic characteristics, subjective well-being and some indicators of anxiety, stress and depression of Colombian students in Brazil. 173 graduate students participated (48.6% male, 51.4% female, ages M=30,34 DP=5.13, master = 47.39%, doctorate= 47.39% and post-doctorate= 5.22%) which were recruited by social networks, curriculum platforms and some institutions and programs which promote research. Data collection was conducted through an online survey that included a Biosociodemographic questionnaire, the Depression, Anxiety, Stress Short Form Scale- (DASS-21) Satisfaction with life Scale (SWLS) and of Positive and Negative Affection scale (PANAS). Results presented normal levels of anxiety, stress, depression, positive and negative affect, were found, and in most cases, high life satisfaction. The Student's t and Chi Square tests showed no statistically significant differences for the above variables between masters and doctoral students. These findings provide an initial insight regarding the situation of Colombian students, which can be useful for future support in their academic processes linking to Brazilian universities.